Enseñanza de los medios de transporte a vapor de la primera revolución industrial a través del videojuego “Minecraft” en octavo grado en el colegio Gabriel Betancourt Mejía (2022)
In this work a didactic material was developed to address the disinterest of students in learning new topics and in turn seeks to help the teacher to explore new resources to implement in the classroom